2021
DOI: 10.3389/fpsyg.2021.580351
|View full text |Cite
|
Sign up to set email alerts
|

Change Process in Coaching: Interplay of Nonverbal Synchrony, Working Alliance, Self-Regulation, and Goal Attainment

Abstract: Background: Psychological literature emphasizes that self-regulation is important as goal intentions, goal setting, or implementation intention does not automatically result in effective results in coaching. The question which coaching strategies to apply to strengthening clients' self-regulatory capacities as prerequisites of effective change outcomes remains a black box in coaching.Method: This quantitative study explored clients' self-regulatory mechanisms by addressing how nonverbal synchrony influences cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 126 publications
(191 reference statements)
1
46
0
Order By: Relevance
“…Therefore, we are interested in building knowledge of MS as a time-series measure as a yet unexplored phenomenon in the coaching process. All the more, as the study by Erdös and Ramseyer ( 2021 ) indicated that MS may have a rich nature and multilayered facets for coaching as an interactional change process, hence, we claim that digging deeper into the serial representation of MS may be useful to yield insights that can be further investigated in coaching research on the basis of hypothesis-testing studies or in applying descriptive approaches to enhance our understanding of coaching as a change process.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Therefore, we are interested in building knowledge of MS as a time-series measure as a yet unexplored phenomenon in the coaching process. All the more, as the study by Erdös and Ramseyer ( 2021 ) indicated that MS may have a rich nature and multilayered facets for coaching as an interactional change process, hence, we claim that digging deeper into the serial representation of MS may be useful to yield insights that can be further investigated in coaching research on the basis of hypothesis-testing studies or in applying descriptive approaches to enhance our understanding of coaching as a change process.…”
Section: Introductionmentioning
confidence: 86%
“…Movement synchrony (MS; Ramseyer and Tschacher, 2011 ) is a yet unexplored concept in coaching. To date, the only study investigating MS as a spontaneous non-verbal interactional variable beyond consciousness in workplace coaching (Erdös and Ramseyer, 2021 ) found MS to have implications for clients' affective and cognitive regulatory capacities. That study also found MS to be influenced by the quality of the coach-client relationship in clients' goal-striving processes.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 3 more Smart Citations